The effects of Calorie restriction and Bariatric surgery on Circulating Proneurotensin levels - Miskelly, Michael G (Oxford University Press, 2025)
Context
Proneurotensin (pNT) is associated with obesity and type 2 diabetes (T2D), but the effects of Roux-en-Y gastric bypass (RYGB) on postprandial pNT levels are not well studied.
Objective
This work aimed to assess the effects of RYGB vs a very low-energy diet (VLED) on pNT levels in response to mixed-meal tests (MMTs), and long-term effects of RYGB on fasting pNT.
Methods
Cohort 1: Nine normoglycemic (NG) and 10 T2D patients underwent MMT before and after VLED, immediately post RYGB and 6 weeks post RYGB. Cohort 2: Ten controls with normal weight and 10 patients with obesity and T2D, who underwent RYGB or vertical sleeve gastrectomy (VSG), underwent MMTs and glucose-dependent insulinotropic polypeptide (GIP) infusions pre surgery and 3 months post surgery. Glucagon-like peptide-1 (GLP-1) infusions were performed in normal-weight participants. Cohort 3: Fasting pNT was assessed pre RYGB (n = 161), 2 months post RYGB (n = 92), and 1year post RYGB (n = 118) in NG and T2D patients. pNT levels were measured using enzyme-linked immunosorbent assay.
Results
Reduced fasting and postprandial pNT were evident after VLED and immediately following RYGB. Reintroduction of solid food post RYGB increased fasting and postprandial pNT. Prior to RYGB, all patients lacked a meal response in pNT, but this was evident post RYGB/VSG. GIP or GLP-1 infusion had no effect on pNT levels. Fasting pNTs were higher 1-year post RYGB regardless of glycemic status.
Conclusion
RYGB causes a transient reduction in pNT as a consequence of caloric restriction. The RYGB/VSG-induced rise in postprandial pNT is independent of GIP and GLP-1, and higher fasting pNTs are maintained 1 year post surgically.